Dynamic contrast-enhanced magnetic resonance perfusion of the brain in children with craniosynostosis - M. V. Lukin; Ya. A. Filin; A. V. Zvezdin; D. A. Beregovskiy; A. Yu. Efimtsev; G. E. Trufanov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Craniosynostosis is the premature closure of cranial sutures, leading to skull deformation, cranio-cerebral disproportion, and potentially resulting in the development of intracranial hypertension, persistent neurological, and cognitive impairments. Magnetic resonance imaging (MRI) complemented by dynamic contrast-enhanced MR perfusion, allows for a detailed assessment of intracardiac structures, as well as evaluation of cerebral blood flow parameters in areas of suspected brain compression in children with craniosynostosis. Purpose of the study: еvaluate cerebral blood flow parameters (CBV and CBF) in children with craniosynostosis using contrast-enhanced dynamic MR perfusion in the preoperative stage. Object and methods. Forty-eight children with various types of craniosynostosis were examined: 10 (20%) had sagittal suture synostosis, 15 (31%) had metopic suture synostosis, 9 (19%) had unilateral coronal suture synostosis, 6 (13%) had bicoronal synostosis, 2 (4%) had lambdoid synostosis, and 6 (13%) had involvement of all sutures. Color perfusion maps of CBF and CBV were constructed using the syngo.via system (Siemens). Results. According to MR perfusion data, in areas of compression (frontal lobes) relative rCBV and rCBF indices in metopic craniosynostosis were 88.3 ± 24.6% and 85.5 ± 19.6% respectively, compared to the occipito-parietal regions. In cases of unilateral coronal synostosis, in the compression zone (ipsilateral frontal lobe) relative to the contralateral frontal lobe, they were 95.3 ± 3.1% (rCBV) and 93.1 ± 2.2% (rCBF), and relative to the occipital lobes, 84.4 ± 5.2% (rCBV) and 87.3 ± 8.2% (rCBF). In cases of bicoronal synostosis, in the frontal lobes they were 86.2 ± 19.7% (rCBV) and 86.4 ± 14.7% (rCBF) relative to the occipito-parietal regions. In cases of sagittal suture closure, in the temporal lobes relative to the frontal and occipital lobes, they were 99.1 ± 3.2% (rCBV) and 98.1±2.4% (rCBF).